Electrolyte‐Gated Organic Field‐Effect Transistor Sensors Based on Supported Biotinylated Phospholipid Bilayer. (3rd January 2013) - Magliulo, Maria; Mallardi, Antonia; Mulla, Mohammad Yusuf; Cotrone, Serafina; Pistillo, Bianca Rita; Favia, Pietro; Vikholm‐Lundin, Inger; Palazzo, Gerardo; Torsi, Luisa
<x xml:space="preserve">Abstract</x> Anchored, biotinylated phospholipids forming the capturing layers in an electrolyte‐gated organic field‐effect transistor (EGOFET) allow label‐free electronic specific detection at a concentration level of 10 nM in a high ionic strength solution. The sensing mechanism is based on a clear capacitive effect across the PL layers involving the charges of the target molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>